2021
DOI: 10.1210/clinem/dgab712
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Fractures in Congenital Adrenal Hyperplasia: A Swedish Population-based National Cohort Study

Abstract: Context Low bone mineral density has been reported in individuals with congenital adrenal hyperplasia (CAH), but the prevalence of fractures is unclear. Objective To study the prevalence of fractures in CAH. Design, Setting, and Participants: Patients with CAH (n=714, all 21-hydroxylase deficiency) were compared with controls matched for sex and year and place of birth (n=71,400). Data were derived by linkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…As far as the metabolic outcomes and complications such as obesity, cardiovascular complications, and bone fragility, they are mostly associated with the therapy; therefore, delineating the influence of genotype is very complicated due to different treatment regimens and length of therapy. However, the risk is generally increased as compared with controls ( 92 95 ). In one large epidemiological study, only obesity and venous thromboembolism were significantly more common in patients with In2G than in controls, while patients with null variants had more cardiometabolic risk ( 96 ).…”
Section: Cyp21a2 In2g Variantmentioning
confidence: 97%
“…As far as the metabolic outcomes and complications such as obesity, cardiovascular complications, and bone fragility, they are mostly associated with the therapy; therefore, delineating the influence of genotype is very complicated due to different treatment regimens and length of therapy. However, the risk is generally increased as compared with controls ( 92 95 ). In one large epidemiological study, only obesity and venous thromboembolism were significantly more common in patients with In2G than in controls, while patients with null variants had more cardiometabolic risk ( 96 ).…”
Section: Cyp21a2 In2g Variantmentioning
confidence: 97%
“…A meta-analysis of nine case–control studies ( n = 254 patients with CAH and 344 control individuals) showed a lower BMD in patients with CAH; however, a relationship with glucocorticoid dose was not found 90 . A population-based Swedish study ( n = 714 patients with CAH and 71,400 control individuals) found an increased risk of fragility fractures in patients with CAH 91 . Overall, BMD studies in CAH are limited to either small cohorts or heterogeneous cohorts lacking hormonal data, thereby highlighting the need for rigorous prospective studies.…”
Section: Management Challengesmentioning
confidence: 99%
“…In a meta-analysis, including individuals with glucocorticoid replacement therapy, treatment increased the fracture risk [ 57 ]. Recent epidemiological studies on the presence of fractures in patients with CAH have been reported [ 33 , 58 ]. A Swedish study identified more fractures in the patient group already at a young age compared to the general population (OR, 1.61; mean age of the CAH group 29.8 years) [ 58 ].…”
Section: Bone Healthmentioning
confidence: 99%
“…Recent epidemiological studies on the presence of fractures in patients with CAH have been reported [ 33 , 58 ]. A Swedish study identified more fractures in the patient group already at a young age compared to the general population (OR, 1.61; mean age of the CAH group 29.8 years) [ 58 ]. However, in a Korean study, more fractures were only found in patients aged 40 years and older (OR, 1.4) [ 33 ].…”
Section: Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation